Menyoal Pengelolaan Keuangan Publik Dalam penanganan Pandemi Covid-19 di Indonesia - Rusman Ghazali (Universitas Nasional, 2023)
This research is a study on public finance in handling Covid-19 in Indonesia. The problem is that public financial management is not in harmony with the humanitarian threats faced by the people. The purpose of the study is to assess the allocation of state finances by the government in handling the Covid-19 pandemic. The theoretical approach refers to the concept of public finance managed by policy-making actors. This study uses a descriptive-qualitative method that relies on secondary data. The results of the study revealed that the allocation of state finances by the government in handling the Covid-19 pandemic does not give priority to the health sector directly, but instead is allocated to the economic recovery sector, although it is recognized that the Covid-19 pandemic causes complexity of public problems in other economic and socio-cultural fields, and has implications for various forms of corrupt practices. Despite the government's limitations in overcoming the complexity of the problem of handling the Covid-19 pandemic, the government still benefits from the socio-cultural capital of the Indonesian people to help each other deal with the Covid-19 pandemic. The conclusion is that public financial management for its allocation to the interests of the people is not guided by the principles of transparency and accountability, because the regulations made by actors in handling the Covid-19 pandemic actually overlap a lot. Penelitian ini adalah studi tentang keuangan publik dalam penanganan pandemi Covid-19 di Indonesia. Masalahnya, pengelolaan keuangan publik tidak selaras dengan ancaman kemanusiaan yang dihadapi. Tujuan studi, untuk menilai peruntukan keuangan negara oleh pemerintah dalam menangani Covid-19. Pendekatan teori mengacu pada konsep keuangan publik yang dikelola oleh aktor pembuat kebjakan. Kajian ini menggunakan metode deskriptif-kualitatif yang bertumpu pada data sekunder. Hasil studi mengungkap, bahwa peruntukan keuangan negara oleh pemerintah dalam menangani pandemi Covid-19 tidak memberi prioritas pada sektor kesehatan secara langsung, namun justru lebih besar dialokasikan pada sektor pemulihan ekonomi, meskipun diakui bahwa pandemi Covid-19 menyebabkan timbulnya kompleksitas masalah publik pada bidang ekonomi dan sosial-budaya lainnya, dan berimplikasi pada berbagai bentuk praktik korupsi. Meskipun demikian, keterbatasan pemerintah mengatasi kompleksitas masalah penanganan pandemi Covid-19, pemerintah masih diuntungkan modal sosial-budaya masyarakat Indonesia untuk saling membantu menghadapi pandemi Covid-19. Kesimpulan, bahwa pengelolaan keuangan publik untuk alokasinya pada kepentingan rakyat tidak dipandu asas transparansi dan akuntabilitas, karena regulasi yang dibuat para aktor dalam menangani pandemi Covid-19 justru banyak yang tumpang-tindih.